Digital Transformation In Education Administration at PGRI Silampari University - Yuneti, Armi; Amin, Ahmad (Jurnal Mamangan, 2025)
Digital Transformation in Education Administration at PGRI Silampari University. This study aims to examine the level of digital transformation implementation, the challenges faced, and its impact on the effectiveness of educational administration at PGRI Silampari University. The background of this study is based on the importance of digitization in improving the efficiency, transparency, and quality of higher education administration services, especially in developing regions. The research method used is quantitative with a survey approach. The research sample consisted of 60 respondents, including educational staff, lecturers, and students from PGRI Silampari University. The research instrument was a closed-ended questionnaire with a 1–5 Likert scale, measuring four main variables: digital technology utilization, administrative service effectiveness, digital literacy of human resources, and user satisfaction. Data analysis was conducted using descriptive statistics. The research results obtained were: digital technology utilization with an average score of 3.9 (good category), with most respondents assessing that the digital-based administrative system was already in use, although not yet optimal; administrative service effectiveness with an average score of 3.8 (good category) with faster service processes but still facing technical challenges, digital literacy of human resources scored an average of 3.5 (moderate category) with a gap in digital application usage skills, particularly among educational staff, and user satisfaction scored an average of 3.7 (good category) with users feeling assisted but hoping for a more integrated system. It can be concluded that the level of digital transformation implementation at PGRI Silampari University is good but not yet optimal. The use of digital technology has a significant effect on the effectiveness of administrative services, while the digital literacy of human resources has a positive effect on user satisfaction. The main challenges include limited digital literacy, technological infrastructure, and resistance to change.